2019
DOI: 10.5194/acp-19-3287-2019
|View full text |Cite
|
Sign up to set email alerts
|

The two-way feedback mechanism between unfavorable meteorological conditions and cumulative aerosol pollution in various haze regions of China

Abstract: Abstract. Accompanied by unfavorable meteorological conditions with stable stratification in various haze regions of China, persistent heavy aerosol pollution episodes (HPEs) lasting more than 3 consecutive days frequently occur, particularly in winter. In the North China Plain (NCP), explosive growth of fine particulate matter smaller than 2.5 µm in diameter (PM2.5), which occurs during some HPES, is dominated by a two-way feedback mechanism between more unfavorable meteorological conditions and cumulative ae… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(67 citation statements)
references
References 33 publications
3
62
1
1
Order By: Relevance
“…(Haze-I) and 1% (Haze-II) reported in this study (Figure 4), suggesting that the contribution of industrial emissions to regional haze in Northeast China is much smaller than that in the NCP. Many studies have summarized formation mechanisms of general regional haze in North China: regional transport of air pollutants (Zheng et al, 2015b), massive formation of secondary aerosols (Shao et al, 2019), and two-way feedback between adverse meteorological conditions and pollutant accumulation (Zhong et al, 2019). We found that the Haze-I formation in this study can be attributed to these three formation mechanisms (Figure 8).…”
Section: Comparison: Haze In Northeast China Vs Ncpmentioning
confidence: 51%
See 3 more Smart Citations
“…(Haze-I) and 1% (Haze-II) reported in this study (Figure 4), suggesting that the contribution of industrial emissions to regional haze in Northeast China is much smaller than that in the NCP. Many studies have summarized formation mechanisms of general regional haze in North China: regional transport of air pollutants (Zheng et al, 2015b), massive formation of secondary aerosols (Shao et al, 2019), and two-way feedback between adverse meteorological conditions and pollutant accumulation (Zhong et al, 2019). We found that the Haze-I formation in this study can be attributed to these three formation mechanisms (Figure 8).…”
Section: Comparison: Haze In Northeast China Vs Ncpmentioning
confidence: 51%
“…In China, regional heavy hazes frequently occur in the North China Plain (NCP) (Zhao et al, 2013) and Northeast China (Ma et al, 2018) during winter. In the past decades, the regional haze formation mechanisms in the NCP have been intensely investigated (Chen et al, 2017b;Cheng et al, 2016;Li et al, 2015;Liu et al, 2017c;Tao et al, 2014;Tian et al, 2015;Wang et al, 2016;Wang et al, 2019;Wang et al, 2014;Xing et al, 2019;Zheng et al, 2015b;Zhong et al, 2019). Adverse meteorological conditions (e.g., low wind speeds and stable atmospheric boundary layer ) can induce preliminary formation of hazes during winter (Zheng et al, 2015b;Zhong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…研究 还显示, 该反馈机制与气溶胶浓度密切相关, 当气溶胶 浓度较低时反馈效应不明显, 而当气溶胶浓度较高时 反馈效应显著增加 [65] . Zhong等人 [125] 味 着 液 相 非 均 相 反 应 在 气 -粒 过 程 中 发 挥 主 导 作 用 [13,70] . Liu等人 [70] 的研究显示, 边界层高度的下降在 [126] ; 二是气溶胶粒 子作为云凝结核改变云的物理和微物理特征, 改变云 的辐射特征和降水过程, 影响太阳能在地气系统中的 分配(间接效应) [127~130] .…”
Section: 气溶胶与多尺度过程的相互作用unclassified